Prioritizing the Issues extracted for Getting Right People on Right Project in Software Project Management From Vendors’ Perspective - Majid Hussain; Habib Ullah Khan; Abdul Wahid Khan; Siffat Ullah Khan (IEEE Access)
Software project management inspires and urges the spirit of software developing team members which continues until project completion. Obviously, success of every project based on right selection of team members that ensures to meet the desired requirements of any software developing project. The fundamental aim of current study is to extract and prioritize issues faced by vendors of global software development (GSD) organizations during the selection of right team with having aim to complete the project successfully. As a methodology, a systematic literature review (SLR) used for data extraction and categorization, a questionnaire survey adopted for data validation, and a hierarchical analytical process (AHP) used for prioritizing extracted findings. A total of 12 issues are extracted and grouped into 3 categories (association, teamwork, and fascination). The overall result showed that “association” is the most important category as compare to other categories. Similarly, communication and coordination issues, team’s consistency and stability issues, and lack of expertise issues, etc are highlighted as the most critical issues during selection of right people for the right project from vendors’ perspective.